The spatial distribution characteristics of typical pathogens and nitrogen and phosphorus in the sediments of Shahe Reservoir and their relationships - Wen Sun (Nature Portfolio, 2021)
Abstract Using samples collected in Shahe Reservoir in the upper North Canal in China, this research analyzes the structure of a microorganism group in sediment and the absolute abundance of two typical pathogenic bacteria (Escherichia coli and Enterococcus), and their relationship with environmental factors including total nitrogen (TN) and total phosphorus (TP). The study of samples collected from the surface (0–20 cm) and sediment cores shows that the absolute abundance of E. coli in horizontal distribution in the sediment is highest in downstream of the reservoir and point source pollution area. In vertical distribution, the absolute gene expression level of the two pathogenic bacteria in the sediment tends to decrease with increasing depth, although its highest value at 10–30 cm depth. The relative abundance the two pathogenic bacteria is much greater in the sediment of Shahe Reservoir with the structure of horizontal groups including Clortridium sensu stricto, unclassified Anaeroineaceae, and Povalibacter, while Anaeroineaceae is much more abundant in the group structure of the vertical distribution. Pearson correlation analysis suggests positive correlation in horizontal distribution for E. coli and TN and TP (P < 0.05) and for Enterococcus and TP (P < 0.05). The results clearly show that the amount of pathogenic bacteria in the sediment in Shahe Reservoir is most likely due to water eutrophication.